Gender Pay Gap Patterns in Domestic and Foreign-Owned Firms - Iga Magda; Katarzyna Salach (Institute of Labor Economics (IZA), 2019)
We investigate differences in gender wage gaps between foreign-owned and domestically-owned firms in Poland, a country that has experienced large FDI inflows over the past three decades. In line with the findings of several other studies, we show that according to standard estimates of adjusted gender wage gaps, these differences are much larger in the foreign-owned companies than in the domestic firms. However, we also find that these estimates cannot be trusted because the domestically-owned firms have considerably higher levels of gender segregation, and because the OLS estimates of the adjusted gender wage gaps in this sector are more likely to be biased. Using a matching and decomposition technique (\~Nopo 2008) that allows us to capture gender wage differentials over a common support, we find that gender wage gaps in domestically-owned firms are only slightly smaller than those in foreign-owned companies. Our results also indicate that women tend to segregate into low-paid jobs in the domestic sector, whereas there is no evidence of such a pattern in the foreign sector. The analysis furthers shows, however, that foreign-owned companies have much larger within-firm differences in earnings (net out of composition effects), and that these earnings they pay vary less across firms. In sum, we find that the nature of gender wage gaps and the factors that underlie them differ between domestic and foreign-owned companies.
Keywords: F23; J16; J31; J71; 330; gender wage gaps; domestic ownership; foreign ownership; FDI